2018
DOI: 10.1177/1129729817747532
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration and extravasation in pediatric patients: A prevalence study in a children’s hospital

Abstract: The infiltration and extravasation prevalence were found to be high, but the interventions to address them were inadequate. Training and implementation strategies should be planned for pediatric nurses to prevent infiltration and extravasation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…4,5 The complications caused by intravenous infusion are more common compared to those of central infusion-with varied numbers of infiltration/extravasation (2.9%-69.89%), phlebitis (16.7%-25.4%), and obstruction (12.27%) incidences. [6][7][8][9][10] The causative factors of phlebitis are the effects of total parenteral nutrition (TPN), antibiotics, infection, weight, blood transfusion, and the devices used. 7,8,[11][12][13] Nurses play an important role in performing intravenous insertion in neonates to prevent phlebitis.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The complications caused by intravenous infusion are more common compared to those of central infusion-with varied numbers of infiltration/extravasation (2.9%-69.89%), phlebitis (16.7%-25.4%), and obstruction (12.27%) incidences. [6][7][8][9][10] The causative factors of phlebitis are the effects of total parenteral nutrition (TPN), antibiotics, infection, weight, blood transfusion, and the devices used. 7,8,[11][12][13] Nurses play an important role in performing intravenous insertion in neonates to prevent phlebitis.…”
Section: Introductionmentioning
confidence: 99%
“…A ocorrência de extravasamento nas CIP realizadas em crianças e adolescentes atingiu uma taxa de 8,7%, estando na faixa observada na literatura nacional e internacional da área pediátrica, que varia de 1,79% a 78%. (9,(12)(13)(14)(15) Ainda que a taxa de extravasamento em crianças esteja em concordância com a literatura nacional e internacional, acredita-se na necessidade de se estabelecer cuidados clínicos baseados em evidências científicas para a promoção de uma prática segura, e que medidas de prevenção desta complicação em crianças sejam tomadas, promovendo, assim, a segurança do paciente. Neste sentido, a realização de práticas seguras garante a qualidade na assistência à saúde, reduz a ocorrência de eventos adversos e diminui o tempo de hospitalização.…”
Section: Discussionunclassified
“…1 Previous research has demonstrated PIVC dysfunction, including extravasation, results in the premature failure of up to 40% of PIVCs in children. [2][3][4][5] Critically ill children are especially vulnerable to extravasation injuries due to their exposure to multiple high-risk drugs, difficulties in vascular access and the common use of sedation, which may…”
Section: Introductionmentioning
confidence: 99%